Exosomal non-coding RNAs in glioma progression: insights into tumor microenvironment dynamics and therapeutic implications - Marangon, Davide; Lecca, Davide (Frontiers in Cell and Developmental Biology, 2023)
Gliomas are the most common and deadly types of brain tumors, known for their extensive genetic and epigenetic variability, which poses considerable challenges for pharmacological treatment. Glioma heterogeneity is also related to their intricate and dynamic tumor microenvironment (TME), which comprises a diverse array of cell types, including immune cells, vascular cells, glial cells, and neural precursors, collectively influencing tumor behavior and progression. A pivotal aspect of this intercellular communication relies on the exchange of extracellular vesicles (EVs), which contain and transfer complex molecular cargoes typical of their cells of origin, such as proteins, lipids, carbohydrates, metabolites, and non-coding RNAs (ncRNAs), that encompass microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs). Glioma cells actively release EVs loaded with specific ncRNAs that can target genes and other ncRNAs in recipient cells residing within the TME. Among these recipient cells, prominent players include tumor-associated macrophages and microglia (TAMs), non-neoplastic astrocytes and endothelial cells. The intricate interplay between EVs derived from glioma cells and these recipient cells significantly contributes to the establishment of a tumor-permissive microenvironment, promoting tumor cell proliferation, migration, angiogenesis, and invasion by targeting various downstream pathways. This review critically examines the current understanding of the intricate interplay between glioma, exosomal ncRNAs, and various components of the glioma TME. By shedding light on the roles of ncRNAs in mediating intercellular communication, this review underscores their significance in orchestrating TME transformation and highlights their potential as novel therapeutic targets for effectively tackling glioma progression.